Tax policies in a transition to a knowledge-based economy: The effective tax burden of companies and highly skilled labour - Leonie Fischer; Jost H. Heckemeyer; Christoph Spengel; Daniela Steinbrenner (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
Globalisation and the fast-approaching digitalisation increase capital as well as labour mobility fostering tax competition among countries worldwide. Based on a unique dataset, we analyse the development of effective tax burdens on corporations and highly skilled labour for 26 OECD countries over the last decade. The synthesis of both indicators allows us to identify tax strategies of the countries considered and to further elaborate on the scope of future tax competition against the background of current developments. Overall, we find a declining trend in effective tax burdens on corporate investments, whereas we observe increases in the top statutory tax rates for high-income earners and a rather constant average effective tax burden on labour for a disposable income of EUR 100'000. Current developments like the agreement on a global minimum tax or the transition to a knowledge-based economy can set a new lower bound to tax competition on corporate investments and might shift its focus.
Keywords: H21; H25; 330; effective tax rates; tax competition; location attractiveness; corporate location decision; Devereux/Griffith Methodology; Human Resource Tax Analyzer